(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
Gynecological diseases remain a significant public health concern among women of reproductive age and contribute substantially to morbidity, reduced quality of life, and adverse reproductive outcomes. Preventive healthcare services play a crucial role in early detection, risk reduction, and timely management of gynecological conditions. Women’s consultation clinics represent a key component of primary healthcare systems, providing accessible reproductive health services, preventive examinations, health education, and counseling. This study aims to evaluate the role and effectiveness of women’s consultation clinics in the prevention of gynecological diseases among women of reproductive age. Particular attention is given to preventive strategies, including routine gynecological examinations, screening programs, health education, and early diagnosis. The study analyzes how organizational structure, accessibility of services, and patient awareness influence preventive outcomes. Understanding the contribution of women’s consultation clinics to gynecological disease prevention may support the development of improved healthcare strategies and enhance reproductive health outcomes in women.